An Educational Experiment Resulting from COVID‐19: The Use of At‐Home Waxing and Webinars for Teaching a 3‐Week Intensive Course in Tooth Morphology to First Year Dental Students. Issue 3 (6th January 2021) - Goodacre, Charles J.; Younan, Reema; Kearbey, Vaughn; Fitzpatrick, Michael
Abstract: Purpose: To report the outcomes of presenting a 3‐week intensive course in tooth morphology to first year dental students using "at‐home" waxing projects and webinars. Materials and Methods: Students were provided with the instrumentation and materials required to complete 5 waxing projects at home during the 3‐week course. In the same time period, the didactic content was presented via 11 webinar sessions. A postcourse survey provided student perspectives regarding this new experience. Results: Students were able to effectively complete high‐quality waxing projects at home by using step‐by‐step images and videos but the survey indicated an overwhelming preference for in‐person faculty feedback. Webinars based on the students having studied the 3D Tooth Atlas and an instructor reviewing content in the Atlas was effective in teaching the didactic aspect of tooth morphology as evidenced by the student grades and survey results. However, most of the students indicated a preference for physically going to class and being able to interact with faculty and classmates as opposed to online webinars. The condensed 3‐week version of the course was part of an expanded 4‐week student orientation and worked well, allowing other clinical precursor courses to occur before their usual time in the curriculum, thereby allowing students to begin earlier patient treatment. Conclusions: The at‐home waxing exercises produced very good results by having the students use step‐by‐step images and videos in the 3D Tooth Atlas. However, the students indicated a strong preference for personal faculty feedback that was not available at home. Students effectively learned the didactic aspects of tooth morphology through the webinars with accompanying use of the 3D Tooth Atlas but again most students prefer physically going to class and being able to interact with faculty and classmates. These preferences for contact with classmates and faculty supports the natural human desire for personal interactions with other human beings.